A escrita para o outro no processo de alfabetização - Costa, Dania Monteiro Vieira (2013)
The paper integrates studies developed in the language area, in an enunciative-discursive approach, though the Education and Languages research line of the Post-Graduation Education Program of the Federal University in the State of Espírito Santo. It is about a study-case that aims at discussing the following thesis: in the beginning process of literacy, the children write texts in order to dialogue among each other. It was held in an Elementary School institution in the district of Vila Velha/ES. The work is based on the bakhtinian language approach, mainly on the instruction idea discussed by Bakhtin and on Vigotski contributions regarding the relation between development and learning, postulating that learning the written language cannot be laid on the processes that must be mature in the children, because those processes are constituted during that learning. The study sees that the domination of the skills to read and write is not a requirement for the production of texts, however, it is through the production of texts that the children appropriate the written language fully: as in form and discourse. It analyzes the texts produced by children, at school, from the interlocutors chosen by them, constituting the following categories: in the first one, named Writing for the others: the emergency of an interlocutor, the work analyzes an event, which there is a dialogue with the children about the possibility to write for a fairy tale character; in the second one, titled Writing for the others: the dialogue with family, it analyzes events, which the children wrote for their relatives (mother, father, uncles, aunts, cousins and others); in the third and last category, Writing for the others: the dialogue with friends, it is discussed the texts produced for their mates. The paper concludes that the children when writing with communication purposes make their discursive projects by writing instructions full of their own life stories, their conflicts, affections and wishes. In this context, the children also dialogue about their ideas concerning the writing system, thus reflecting on the discursive and linguistic aspects of the written language